DEVELOPMENT OF MATHEMATICAL SNAKES AND LADDERS MEDIA TO IMPROVE ELEMENTARY STUDENTS' LEARNING OUTCOMES ON CIRCLE MATERIALS - Mohammad Archi Maulyda; Umar Umar; Vivi Rachmatul Hidayati (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2021)
The success of the teacher in creating an interesting learning atmosphere and can foster a positive attitude of students in participating in this learning is strongly influenced by several factors, one of which is the use of interesting learning media. The purpose of this research is to produce Snakes and Ladders Game Learning Media on the Circle material for grade VI students of SDN 26 Ampenan which is suitable for use based on the assessment of Material Experts, Media Experts, and Students, as well as improving student learning outcomes. Snakes and Ladders Game Learning Media was developed using research and development or Research and Development (R&D) with the ADDIE development model. At the Development stage, the media developed was assessed for feasibility by 2 Material Experts (lecturers and teachers), 1 Media Expert, 5 Small Group Trial Students, and 25 Large Group Trial Students. Data collection techniques in this development research are through questionnaires and tests. The data obtained from the questionnaire were analyzed descriptively qualitatively and quantitatively. The results of the media assessment based on the Material Experts obtained an average score of 3.6 included in the